Forensic countermeasures against raiding - Sembekova Б.Р.; Raktaeva А.М. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The article deals with the issues of forensic support of the proving process with effective methods and methods aimed at establishing the conditions and circumstances of criminal activity by revealing the methodology for investigating raiding. The methodology for investigating raiding is disclosed on the basis of an analysis of its characterizing features that determine ways to solve organizational, legal, tactical, and strategic tasks. The criminalistic analysis of criminal raiding is based on the consideration of the mechanism of criminal activity reflected in the situation of commission, and concealment of crimes. The mechanism of criminal activity of raiding, reflected in the environment by ways of committing, ways of concealment, and ways of counteraction is an information tool for the development of forensic methodology aimed at providing the process of proving effective methods of knowledge.